Biosensors for food analysis - Scott, A. O (Royal Society of Chemistry, 2000)
Reviews current status of research & commercial developments in this field. Brings food researchers in industry & the academic world up to date on biosensor technology, & identifies state of the art biosensor applications.
Keywords: biochemie; nutriční terapie, dietoterapie a výživa